Analysis of the Industry 4.0 How Breaking Element in Production Administration - Santos, Ismael Luiz dos; Santos, Ruan Carlos dos; Silva Junior, Daniel de Souza (Future Studies Research Journal: Trends and Strategies, 2019)
The First Industrial Revolution potentiated the power of production through the steam engine, the Second Industrial Revolution, through steel and electricity, gave life to mass production. A Third Revolution can be attributed to the electronic automation of production lines and now, according to SCHWAB (2016), the world is witnessing the Fourth Industrial Revolution based on the digitization of industrial processes. This article takes a history approach of production management thinking demonstrating its evolution over seven periods. Through a bibliographical research will be presented the main elements that make up the Industry 4.0. In addition to analyzing its impact on the seventh period of Production Management.